LANGUAGE EFFECTIVENESS AND FACTORS INFLUENCING SCIENTIFIC WRITING OF INDONESIAN UNDERGRADUATE THESIS - Saniago Dakhi; Horas Hutabarat (University of Kuningan, 2018)
The linguistic feature distinction between written and spoken discourse, like scientific writing, narrative text, discussion text, oral speech, etc. has been a longstanding discussion among scholars. However, there is limited number of studies on Indonesian undergraduate thesis context. This article reports the language effectiveness, i.e. lexical density and grammatical complexity of undergraduate thesis using the Flesch’s Analysis of the Readability of Adult Reading Materials (1974) and the determinant factors influencing them. This descriptive study, applying online system application, was conducted in an Indonesian pseudonym university. Forty-two undergraduate theses were used as data source of lexical density and grammatical complexity, and four English lecturers participated on interview. Results showed that the average lexical density ratio was 42.14 and the grammatical complexity was 14.54. On the other hand, the determinant factors of academic writing holistically encompass; (1) psychological factors including identity awareness, motivation, and conceptual competency, (2) sociocultural factor covering personal experience, and (3) linguistic factors, namely linguistic awareness and application, and mechanical competency. To sum up, three important conclusions are drawn. Firstly, there is no exactly the same lexical density and grammatical complexity across chapters of the undergraduate theses. Secondly, the undergraduate theses are lexically acceptable, but grammatically are not as they are interpreted as American students’ slick fiction product. Finally, variables affecting academic writing are not only linguistic factors, but also psychological and sociocultural ones.Keywords: lexical density; grammatical complexity; undergraduate thesis; Indonesian context; academic writing; language effectiveness.